Nonverbal communication of young players in team sports - C.L. Pop; M.V. Zamfir (IP Iermakov S.S., 2020)
Background and study aim : Nonverbal communication is always present in sport teams' competition, on the court and around the court. This paper purpose is to investigate the nonverbal skills in two elite basketball cadet teams. Material and Methods: Pursuing this goal, we applied the PONS test to a group of 38 young basketball players 15 -16-year-old: 20 girls and 18 boys. The teenagers were members of Romanian national cadet teams having at least 3 years up to 7 years of experience playing basketball. The test applied to this sample was The Profile of Nonverbal Sensitivity. The test results were statistically analysed aiming to evaluate the nonverbal decoding accuracy of each evaluated athlete and to identify the possible differences between the two teams: boys and girls. Results : There is a statistically significant difference between the two teams in boys' favor, meaning that the girls have done lower average general scores. In decoding face cues both teams are almost equal, de difference relay on understanding the body movement and attitude. Conclusions: Due the scores obtained by the tested players we can conclude that their nonverbal skills are at high level. Training nonverbal communication potentially enhanced game planning and building into the team a healthy psychological and social environment.